A cross-sectional study of the knowledge and screening practices of diabetes among adults in a south western Nigerian city (2021)
Introduction. The control of diabetes depends largely on preventive actions often influenced by knowledge and awareness of the condition, its risk factors, complication, and management. This study assessed the awareness, knowledge, and practices regarding diabetes among adults in two communities in Ibadan, Nigeria. Methods. A community-based cross-sectional study was conducted among five hundred randomly selected non-diabetic respondents, aged 18 to 65 years. Data was collected using the pretested, modified version of the WHO STEPS instrument translated into Yoruba language. Data collected were analysed using descriptive and inferential analysis and the level of significance was set at p < 0.05. Results. Majority of the respondents (89.6%) had previously heard about diabetes. Of these (n = 448), 31.8% were knowledgeable about diabetes and only 28% have ever had their blood glucose level measured by a doctor or other health professionals. Sex and monthly income were statistically associated with respondents’ diabetes knowledge while age, religion, monthly income, employment status, marital status, ethnicity and level of education were statistically associated with screening practices (p < 0.05). Monthly income was found to be a significant predictor of the level of knowledge adjusted by sex. Earning N20,000 ($ 52.60) or less had higher odds of being knowledgeable compared to earning no income (OR 0.54, CI 0.35, 0.83). Conclusion. Though Diabetes awareness is high, knowledge gaps and poor screening practices is of concern. This calls for tailored multi-component, community-based, health education interventions.